A comprehensive review on coupling different types of electrolyzer to renewable energy sources. (1st September 2018) - Mohammadi, Amin; Mehrpooya, Mehdi
Abstract: Fossil fuels cannot provide all the required energy in future due to their exhaustibility. Their utilization also leads to huge environmental problems. Therefore, it is vital to find a new inexhaustible and clean source of energy which could be easily stored and transported. Hydrogen produced by renewable energy sources has all the above mentioned advantages. There are many hydrogen production methods which could be coupled with renewable energy sources. Among them, electrolysis process is the most mature one. In this paper, a review is performed on different methods of coupling electrolyzer systems with different renewable energy sources, including solar energy, wind energy, geothermal energy, ocean thermal energy conversion system and hydroelectric energy. The focus of this study is on how these systems can be integrated and which one has the highest total efficiency. Finally, cost of hydrogen production by different energy sources is compared. Highlights: Hybrid electrolyzer system and renewable energy sources are investigated. Method of integration in order to increasing the process efficiency is discussed. Economic analysis of the hybrid hydrogen production systems is presented.